Superconductivity in ruthenium-based layered cuprate RuSr2(Gd2-xCex)Cu2Oz - Yeoh W.K.; Kek C.A.; Abd-Shukor R. (2023)
We report the preparation procedure of RuSr2 (Gd2-x Cex)Cu2Oz (Ru-1222) cuprate superconductors from x = 0.5 to 0.7 using the solid state reaction method. All compositions showed an almost single Ru-1222 phase with tetragonal symmetry in the 14/mmm space group and semiconducting or semi-metallic normal state behaviour. The RuSr2(Gd1.4Ce0.6)Cu2Oz material exhibits the highest transition temperature with Tc onset near 48 K and Tc zero at 30 K. The transition temperature is very much dependent on the preparation procedure and can be further improved by optimizing the doping levels.